2007
DOI: 10.1186/1471-2334-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Do antibiotic-impregnated shunts in hydrocephalus therapy reduce the risk of infection? An observational study in 258 patients

Abstract: Background: Shunt infection in hydrocephalus patients is a severe, even life-threatening complication. Antibiotic-impregnated shunts (AIS) have been developed in an attempt to reduce rate of shunt infection. The study was performed to analyze if AIS can diminish the rate of shunt infection. The pathogenic nature of shunt infection in patients with AIS systems and those without antibiotic impregnated shunts (non-AIS) was compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 34 publications
2
45
1
6
Order By: Relevance
“…Although 2 earlier studies did not find any effect on infection rates from AIS catheter use, 11,21 larger studies, including meta-analyses, have reported a reduction largely in line with that reported in the present study. 2,[7][8][9][10][12][13][14][15][16][17]20,22,24,28 This study supports previous recommendations made in favor of universal adoption of AISs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although 2 earlier studies did not find any effect on infection rates from AIS catheter use, 11,21 larger studies, including meta-analyses, have reported a reduction largely in line with that reported in the present study. 2,[7][8][9][10][12][13][14][15][16][17]20,22,24,28 This study supports previous recommendations made in favor of universal adoption of AISs.…”
Section: Discussionsupporting
confidence: 87%
“…2,[7][8][9][10][11][12][13][14][15][16][17][20][21][22]24,28 These studies are somewhat heterogeneous in terms of follow-up, patient population (pediatric only, adult only, or mixed), whether primary insertion only or revision surgeries also were included, and in reporting of causative pathogens. Some recent studies have highlighted the possibility of AIS catheters promoting selection of antibiotic-resistant organisms.…”
mentioning
confidence: 99%
“…There is weak evidence that antibiotic-impregnated catheters can reduce the rate of shunt infection, 8,17,23 although the results are mixed. 10,19 An ongoing study of a shunt surgery infection protocol has initial promising results, and is one of the many strategies that are needed to reduce the incidence of shunt infection.…”
Section: Discussionmentioning
confidence: 99%
“…Se han identifi cado diversos factores del paciente y de la atención asociados a una infección de DVP 14 . Entre los factores relacionados con el paciente destacan: prematurez 15 , edad menor de cuatro meses, diagnóstico antenatal de hidrocefalia 16 , enfermedad sistémica concomitante 17 , requerimientos previos de derivativa ventricular externa (DVE), estado de conciencia alterado y uso de terapia oncológica adyuvante (quimioterapia y radioterapia) 15 . También debemos considerar dentro de este grupo la etiología de la hidrocefalia, la cual pudiese llegar a ser un factor predictor en sí mismo de la infección de derivativa.…”
Section: Recibido: 21 De Marzo De 2011unclassified
“…Infecciones Asociadas a Atención de Salud tiempos operatorios prolongados 15,20 y el rasurado de la piel a intervenir 21,22 . Otros factores neuroquirúrgicos identifi cados son: presencia de una fístula de LCR, craneotomía, hipertensión endocraneana (presión intracraneal > 20 mmHg), ventriculostomía de duración prolongada (particularmente en los primeros 7 a 10 días), irrigación del sistema y recambio valvular a repetición 9,17 .…”
Section: Artículo Originalunclassified